The concept of al-wisayah with special reference to the administration of a minor's property under Islamic law and the enacted Islamic law in Malaysia - Badruddin bin Hj Ibrahim (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2006)
This study examines rules governing al-wisāyah in Islamic law with emphasis on the management of a minor's property. This is to demonstrate that the element of trust exists in al-wisāyah of a minor's property, and the role of wasī mukhtār with respect to a minor's property as guardian is also as trustee. This study may contribute to the application of the rules relating to the above element in present time. The statutory provisions of Islamic law in Malaysia on the subject will also be examined to ascertain whether such legislation is adequate as compared to, and in line with Islamic law as propounded by Muslim jurists. This study is mainly a library study. It will discuss the views of the Muslim jurists of the four well-known sunnī schools of law, and contemporary Muslim scholars. The study primarily examines the concept of al-wisāyah in general and the nature of the minor, his legal capacity particularly in respect of disposition of property. It analyses the four essential elements of al-wisāyah in a minor's property: testator, wasī, subject matter and formation. It also examines the function of wasī in the administration of a minor's property especially his duties, powers, rights and liabilities; the issue of the control on wasī in his dealing with a minor's property and his removal; the issue of the termination of al-wisāyah and wasī's duty after its termination. The study predicated that al-wisāyah of a minor's property is also a type of trust where the wasī mukhtār plays a significant role in administering the minor's property under his control. Islamic law in general has provided comprehensive rules regarding to the subject and the statutory provisions of Islamic law in Malaysia, it is suggested, will have to be read in light of Islamic law in general.